Quantum Quadratic Operators and Processes - Mukhamedov, Farrukh; Ganikhodjaev, Nasir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Covering both classical and quantum approaches, this unique and self-contained book presents the most recent developments in the theory of quadratic stochastic operators and their Markov and related processes. The asymptotic behavior of dynamical systems generated by classical and quantum quadratic operators is investigated and various properties of quantum quadratic operators are studied, providing an insight into the construction of quantum channels. This book is suitable as a textbook for an advanced undergraduate/graduate level course or summer school in quantum dynamical systems. It can also be used as a reference book by researchers looking for interesting  problems to work on, or useful techniques and discussions of particular problems. Since it includes the latest developments in the fields of quadratic dynamical systems, Markov processes and quantum stochastic processes, researchers at all levels are likely to find the book inspiring and useful.
Introduction -- Quadratic Stochastic Operators -- Quadratic Processes -- Analytic methods in the theory of quadratic stochastic processes -- Quantum quadratic operators -- Quantum quadratic operators on M2(C) -- Infinite-dimensional quadratic operators -- Quantum quadratic stochastic processes.
Keywords: Dynamics; Ergodic theory; Functional analysis; Operator theory; Probabilities; Dynamical Systems and Ergodic Theory; Functional Analysis; Operator Theory; Probability Theory and Stochastic Processes